Analisis Kinerja Reksa Dana Saham Syariah di Indonesia - Ningrum, Retno Widya; Musadat, Irfan Achmad; Pramayuda, Agung (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
During the Covid-19 pandemic, the JCI produced higher returns compared to the Sharia Stock Mutual Fund Index with quite a large difference in figures. IHSG produced a return of 51.83% while the Sharia Stock Mutual Fund Index only produced a return of 12.85%. This research aims to provide an overview of the mutual fund performance assessment process and analysis of this assessment. There are several methods for assessing investments in portfolio form, including Sharpe Ratio, Treynor Ratio, Jensen's Alpha and Information Ratio. The results showed that in March - December 2020, it was discovered that Panin Dana Syariah Saham  received the highest performance score using two methods, namely the Sharpe ratio and Treynor ratio. In 2021, Panin Dana Syariah Saham received the highest performance score using three methods, namely Sharpe ratio, Jensen's alpha and Information ratio. In 2022, HPAM Ekuitas Syariah Berkah received the highest performance score using three methods, namely Sharpe ratio, Jensen's alpha and Information ratio. In January – June 2023, the Batavia Dana Saham Syariah received the highest performance score using two methods, namely the Sharpe ratio and the Information ratio. However, if you look at the mutual fund that received the highest performance scores during the Covid-19 pandemic, it was Panin Dana Syariah Saham.